ChemInform Abstract: Allene Relay: Palladium‐Catalyzed Bicyclization of Allene‐Propargylic Carbonates with Geminal Bis(nucleophile)s. Issue 10 (11th March 2014) - Ye, Juntao; Ma, Shengming
Abstract An efficient synthesis of fused hetero‐ and carbocycles is presented using the Pd‐catalyzed coupling of allene‐propargylic carbonates with geminal bis‐nucleophiles such as malonoesters, malononitrile, and β‐ketoesters.